Lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) is a substrate of cathepsin-F, a cysteine protease mutated in type-B-Kufs-disease - Peters, Judith; Rittger, Andrea; Weisner, Rebecca; Knabbe, Johannes; Zunke, Friederike; Rothaug, Michelle; Damme, Markus; Berkovic, Samuel F.; Blanz, Judith; Saftig, Paul; Schwake, Michael (Biochemical and biophysical research communications, 2015)
The lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) has been identified as a receptor for enterovirus 71 uptake and mannose-6-phosphate-independent lysosomal trafficking of the acid hydrolase β-glucocerebrosidase. Here we show that LIMP-2 undergoes proteolytic cleavage mediated by lysosomal cysteine proteases. Heterologous expression and in vitro studies suggest that cathepsin-F is mainly responsible for the lysosomal processing of wild-type LIMP-2. Furthermore, examination of purified lysosomes revealed that LIMP-2 undergoes proteolysis in vivo. Mutations in the gene encoding cathepsin-F (CTSF) have recently been associated with type-B-Kufs-disease, an adult form of neuronal ceroid-lipofuscinosis. In this study we show that disease-causing cathepsin-F mutants fail to cleave LIMP-2. Our findings provide evidence that LIMP-2 represents an in vivo substrate of cathepsin-F with relevance for understanding the pathophysiology of type-B-Kufs-disease.